Development of new masks for preventing viral infections - Insuasti Cruz, Erick Vinicio (2021)
Infectious diseases have long shaken global public health due to the characteristics of their transmission mechanisms. Those diseases with the potential to have a high degree of spread are airborne through mucosal droplets that an infected individual ejects from their mouth or nose when talking, coughing, sneezing, or shouting. In the context of the global health crisis due to Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) causing Coronavirus Disease of 2019 (CoViD-19), the entire population has been put in the position to follow specific rules and regulations to prevent the spread of this virus. Personal Protective Equipment (PPE) is one of the alternatives comprising any equipment whose purpose is to protect the user against one or more risks that threaten their safety or health. In this case, one of this equipment is the mask. Mask consists of a physical barrier that prevents droplets, loaded with the pathogenic organism, from entering the individual’s body, initiating a clinical infection process. Currently, certified masks are available on the market with a specific filtration capacity depending on the manufacturing material. However, the acquisition of this equipment by countries with low economic levels is minimal and is a factor that influences the epidemiological curve. Based on this problem, this research aims to optimize the particle filtration capacity of common cotton cloth by coating it with polymeric solutions obtained from plant extracts to obtain an alternative to standard face masks. The fabrics were coated, and their composition was studied through characterization techniques such as FTIR and Raman spectroscopy to evaluate the polymer’s presence in question. The presence of both polymers was confirmed by analysis of the spectra. Once the air filtration tests were performed, it was confirmed that the cotton fabric increased its air retention capacities when coated with the polymer pectin extracted from Passion Fruit (Passiflora edulis) peels. The percentage of air retention reached 73.23% for the highest polymer concentration in solution (25 mg/ml). On the other hand, the same tests performed on the fabric coated with the other polymer-glycosaminoglycan (GAG) extracted from Rosemary (Salvia rosmarinus)- showed different results than pectin. The percentage of air retention reached only 12.03%, only 3.39% more than the uncoated cotton fabric. Polymer-coated cotton fabrics are proposed as an alternative to common face masks due to their increased filtration capacity.